Free jejunum reconstruction of upper esophageal defects. Issue 1 (23rd July 2012) - Laing, Tereze A.; Van Dam, Helena; Rakshit, Kaushik; Dilkes, Mike; Ghufoor, Khalid; Patel, Hasu
Abstract The free jejunum has become an important method for reconstructing extensive oncologic defects of the upper esophagus and pharynx. The advantages of a single‐staged reconstruction with a low incidence of morbidity have generally outweighed criticisms such as the requirement for a laparotomy and poor voice quality. The aim of the study was to present the technique and outcomes of free jejunal reconstruction of the upper esophagus in 31 consecutive cases. We reviewed our experience of free jejunal flaps undertaken over a 6‐year period. Our surgical approach, complications, and results of swallow and speech restoration are described. A functional swallow was achieved by 27/31 patients. However, satisfactory voice restoration was seen in only a small proportion of patients. Complications at the donor site occurred in just one patient. The current review confirms the jejunal flap as a reliable reconstructive option with minimal donor site morbidity. © 2012 Wiley Periodicals, Inc. Microsurgery, 2013.